Clinical, haematobiochemical, radiographic and ultrasonographic features of traumatic reticuloperitonitis in bovines - ATHAR, HAKIM; MOHINDROO, J; SINGH, KIRANJEET; KUMAR, ASHWANI; RANDHAWA, C S (The Indian Journal of Animal Sciences, 2010)
Study was conducted to compare the clinical, haematobiochemical, radiographic and ultrasonographic features of traumatic reticuloperitonitis in bovines. Clinical cases (4 cows and 17 buffaloes) presented with a history of anorexia, fever, decreased milk yield and loss of defecation/scant faeces, were used. Haematological picture revealed neutrophilic leucocytosis with left shift and blood biochemical status showed elevated levels of total protein, albumin, and fibrinogen. Decreased plasma concentration of sodium, potassium and chloride was observed in majority of the cases. Radiographic examination revealed presence of multiple metallic foreign densities in the reticulum of the bovines. Ultrasonographically, morphological changes of reticular wall and reticulophrenic adhesions in cases of localised peritonitis were visualized. The presence of anechoic fluid without echogenic margins, not restricted to reticulum and sometimes with floating fibrinous shreds was observed in cases of diffuse peritonitis. Ultrasonography in B mode and B+ mode found helpful for the diagnosis of traumatic reticuloperitonitis and differentiation of localised peritonitis from diffuse peritonitis.